Theory, Practice and Empirical Analysis of Smart City - Liang, Sun (Indonesian Journal Publisher, 2025)
Smart cities represent the integration of advanced technologies with urban infrastructure to enhance the quality of life, promote sustainability, and improve the efficiency of city services. By leveraging Internet of Things (IoT) devices, data analytics, and artificial intelligence (AI), smart cities enable real-time monitoring and responsive management of transportation systems, energy grids, waste management, and public safety. These cities aim to address the challenges of rapid urbanization by optimizing resource usage, reducing environmental impact, and fostering citizen engagement through digital platforms. The development of smart cities not only transforms traditional urban planning but also plays a critical role in creating resilient, inclusive, and future-ready communities.